Remote mouse control using Android device - Lim, Zheng Wei (2016)
Over the years, smart phones had gradually become part of people daily life. Almost everyone in this modern digital society owns a smart phone. Besides this, more and more gadgets are getting common and cheap. Therefore, it is common for people to own multiple gadgets. Hence, this project aims to reduce the number of gadgets in user possession by integrating as many functions of the gadgets with the smart phone as possible. This shall bring user convenience.